CUSTOMER SATISFACTION FROM PRICE AND PRODUCT QUALITY ASPECT (Case Study on Retail Traders in Daya Grocery Stores) - Mariani Alimuddin; Ifah Finatry Latiep (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This study aims to determine the effect of price and product quality on consumer satisfaction at wholesalers of Daya Wholesale Market stores partially or simultaneously. The type of research used in this study is causal associative research because it analyzes causal relationships. The results showed that price and product quality had a significant effect on consumer satisfaction who shopped at the retail merchants of Pasar Daya Wholesale stores either partially or simultaneously